Cranio-Cerebral Gunshot Wounds to the Head - Walizada , Samsoor; Hadi, Naqibullah (International Journal For Research In Applied And Natural Science, 2021)
Cranio-cerebral gunshots wounds (CCGW) are the most devastating injuries to the central nervous system, especially made by high velocity bullets, the most devastating, severe and usually fatal type of missile injury to the head. The Objective of this article is to investigate and compare, using a retrospective study on Ten cases the clinical outcomes of CCGW. Predictors of poor outcome were: older age, delayed mode of transportation, low admission CGS score with hemodynamic instability, CT visualization of diffuse brain damage, bi-hemispheric, multi-lobar injuries with lateral and midline sagittal planes trajectories made by penetrating high velocity bullets fired from a very close range, brain stem and ventricular injury with intraventricular and/or subarachnoid hemorrhage, mass effect and midline shift, evidence of herniation and/or hematomas, high ICP and/or hypotension, abnormal coagulation states on admission or disseminated intravascular coagulation. Less harmful effects were generated by retained missiles, bone fragments with CNS infection, DAI lesions and neuronal damages associated to cavitation, seizures. 10 patients (8 male and 2 female), age ranged 22-65 years, with CCGW, during the period 2018-2019, caused by military conflict and accidental firing. After initial resuscitation all patients were assessed on admission by the Glasgow Coma Scale (GCS). After investigations: X-ray skull, brain CT, Angio-CT, cerebral MRI, SPECT; baseline investigations, neurological, hemodynamic and coagulability status all patients underwent surgical treatment following emergency intervention. The survival, mortality and functional outcome were evaluated by Glasgow Outcome Scale (GOS) score. As result, referring on 10 cases we evaluate on a retrospective study the clinical outcome, Imagistics, microscopic studies on neuronal and axonal damage generated by temporary cavitation along the cerebral bullet’s track, therapeutics, as the review of the literature. 4 patients with an admission CGS 9 and 10 survived and 6 patients with admission CGS score of 3, with severe ventricular, brain stem injuries and lateral plane of high velocity bullets trajectories died despite treatment. As conclusion, CCGW is the most devastating type of missile injury to the head. Aggressive intensive care management in combination with early management with less aggressive meticulous neurosurgical technique, has significantly reduced the mortality and morbidity associated with these injuries, but they still remain unacceptably high. Primary prevention of these injuries remains important, the patient must be monitored closely for possible complications.